Liquefaction Response and Reinforcement Effect of Saturated Soil Treated by Dynamic Compaction Based on Hydro-Mechanically Coupled Explicit Analysis - Sihan Ma; Guo Zhao; Xiaoyuan Yang; Run Xu; Zhiqiang Weng; Jiawei Liu; Chong Zhou; Chao Li (Buildings, 2025)
In order to accurately analyze the liquefaction and the reinforcement effect of saturated silty and sandy soils treated by dynamic compaction, a hydro-mechanically coupled explicit analysis method was proposed. The method, in combination with the cap model, was carried out using the Abaqus finite element software. Then, parametric analysis was carried out by means of the development and dissipation of excess pore water pressure, effective soil stress and the relative reinforcement degree. And the effects of the drop energy, tamper radius and soil permeability on the liquefaction zone and soil improvement of saturated soil were examined. The results demonstrated that the liquefaction zone and the effective reinforcement were determined by the drop energy rather than the permeability or tamper radius. A 2.5-times increase in drop energy can increase the maximum liquefaction depth by 1.1 m (4.6 m to 5.7 m) and the effective reinforcement depth (Ir ≥ 0.08) by 0.6 m (1.2 m to 1.8 m). It is recommended that the reinforcement effect should be improved by a lower drop energy with a low drop height and a heavy tamper in actual projects. It should also be noted that a smaller tamper radius was conducive to local soil improvement but also generated higher localized excess pore water pressures. Soil permeability critically controls liquefaction potential and excess pore water pressure dissipation. Low permeability soils experienced significant liquefaction depths and slower consolidation, whereas high permeability gravels (k = 10−2 m/s) showed minimal liquefaction and great improvements in depth. To diminish the effect of the underground water, the gravel cushions should be used to drain pore water out before dynamic compaction.